PERAN INSTAGRAM @aldila.aap DALAM MEMBANGUN KEPERCAYAAN DIRI PADA PEREMPUAN - Renita Apriliasari; Siswanta Siswanta (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Slamet Riyadi Surakarta, 2025)
The importance of self-acceptance and diversity, especially among young women, has led to the emergence of social media as an educational and supportive space. The Instagram account @aldila.aap has emerged as one of the media platforms that plays a role in building the self-confidence of its followers through motivational and inspiring messages. This study aims to understand how Instagram content @aldila.aap contributes to building self-confidence. Peter Lauster's Self-Confidence Theory serves as the primaryframework for examining thepsychological changes experienced by followers. This study employs a qualitative, phenomenological approach. The results of the study indicate that the content of @aldila.aap's Instagram account plays a role in building women's self-confidence. Simple content such as short texts and videos can encourage followers, especially women, to be more confident in their abilities, think optimistically, and take responsibility for their life choices. Instagram followers also show development in terms of objectivity, being able to assess themselves realistically and become more rational.Keywords: Role, Instagram, Self-Confidence